Relative Contribution of Monooxygenase and Esterase to Pyrethroid Resistance in Triatoma infestans (Hemiptera: Reduviidae) from Argentina and Bolivia - Santo Orihuela, Pablo Luis (2008)
Recently, high resistance to pyrethroid insecticides has been associated with ineffective field treatments against Triatoma infestans (Klug) in northern Argentina. Samples were collected from two areas in Argentina (Salta and La Rioja) and one in Bolivia (Yacuiba), and were subjected to toxicological and biochemical assays. All populations were resistant to deltamethrin but they showed different profiles to non-pyrethroid insecticides. Salta population showed high resistance ratios (RR) to deltamethrin and only slight differences in the susceptibility to fenitrothion and fipronil compared to the reference strain. Otherwise, La Rioja population showed a lower RR to deltamethrin and no resistance to fenitrothion or fipronil. Finally, Yacuiba population had high a RR to deltamethrin but was susceptibility to fenitrothion and fipronil. In several cases deltamethrin resistant populations had higher susceptibility to bendiocarb than the reference strain. Measured activity of P450 mono-oxygenase in individual insects (based on ethoxycoumarine-O-de-ethylase), tended to be higher in the deltamethrin resistant populations but the differences were not statistically significant. Activity of specific esterases determined by the hydrolysis of 7-coumaryl permethrate, demonstrated an increase in the percentage of insects with higher esterase activity in Salta and La Rioja populations. Unexpectedly, Yacuiba population showed lower pyrethroid esterase activity than the reference strain. The different pyrethroid resistance patterns found in T. infestans from three geographical regions within Argentina and in Bolivia, suggests that enzyme based pyrethroid resistance in this species has multiple origins. Nevertheless, as nerve insensitivity (related to the presence of the kdr gene) is also an important mechanism related to pyrethroid resistance, further studies on the kdr gene should be carried to clarify the relative contribution of each pyrethroid associated mechanism in deltamethrin resistant populations of T. infestans Keywords: Triatoma infestans, insecticide resistance, resistance ratios, mono-oxygenases, pyrethroid esterases.